Implementation of the Independent Curriculum Policy at SDN 152 Cigagak, Bandung City - Anjaswati Titi Nur Azizah; Wulansari; Riska Putri Wulandari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to identify the role of teachers in the implementation of the Independent Curriculum Policy at SDN 152 Cigagak, Bandung City. The general aim of this research is to determine the observation activities carried out by school principals and teachers regarding student development related to the independent curriculum. This type of research is descriptive qualitative research. In this study, the research subjects were the principal and teachers of SDN152 Cigagak. The results of this research show that school principals must be able to guide, direct and inspire all elements of the school to move towards better education in order to produce quality graduates. Under the leadership of a good principal, small schools will progress, these schools will be able to become agents of change which will certainly encourage parents to send their children to that school. By using an independent curriculum, changes can be felt in schools, teachers are more flexible to be as creative in teaching as possible, and are more aware of students' interests, talents, needs and abilities.